Connection to nature - exploring opportunities by the Riverside Glerá in Akureyri, Iceland - Filippusdottir, Lilja (2009)
In this thesis I have decided to take a closer look into my own “backyard”. A river that runs through my hometown, Akureyri, has been a thorn in some people’s side. Glerá river has taken lives but it has also given the town possibilities to develop. Firstly by creating a seaport allowing it to be settled and secondly by giving power to harness electricity. The third gift is its beauty, which needs to be more appreciated.